Digital content & distance sales : new developments at EU level / edited by Ignace Claeys, Evelyne Terryn. - Claeys, I. (Ignace); Terryn, Evelyne (Intersentia, 2017)
Digital Content & Distance Sales analyses three legal instruments proposed by the European Commission in the context of its Digital Single Market Strategy, which has recently become one of its priorities. The proposed instruments are: (1) a directive for the supply of digital content; (2) a directive for the online and other distance sales of goods; and (3) a regulation on cross-border portability of online content services in the internal market. This book takes a combined approach of setting out the broader legislative and political context of the proposed legal instruments, giving the reader a general overview of the background and subsequent impact of the proposals, and in-depth analyses of specific aspects, advantages and challenges. Through this approach, the authors offer valuable insight into key areas of legal development. This book will be useful to academics and practitioners working in contract law, particularly European contract law.